Development and performance evaluation of a chapati pressing machine - AKHILA J. CHAND RASMI JANARDHANAN SANAD S SANDHYA K. R; Dr. Prince M. V (Guide) (Tavanur 2015 Kelappaji College of Agricultural Engineering and Technology)
chapati pressing machine was developmed and fabricated which consists of a frame, power drive, power transmission mechanism and a pressing mechanism. electric motor. shaft.
Development and performance evaluation of a chapati pressing machine